Oxidative stress in fetal programming of cardiometabolic syndrome - Chao, Yung-Mei (2020)
Cardiometabolic syndrome (CMS) is now a disease entity recognized by the World Health Organization. Emerging evidence from both human epidemiological and animal studies indicates that adult CMS may have its origins in early life and can be programmed by intrauterine and early postnatal environments; a phenomenon known as fetal programming of adult disease. This mini-review discusses [1]how exposures to various insults from the mother during gestation and/or lactation programs the fetus that prompts the development of CMS during adulthood; [2] what are the currently known underlying mechanisms, with emphasis on the role of tissue oxidative stress; and [3] whether CMS in the offspring can be reprogrammed via targeting maternal tissue oxidative stress. Translational perspective of the research field is also discussed.